Psychotherapy Within Occupational Therapy Literature: A Scoping Review. (December 2022) - Marshall, Carrie Anne; Murphy, Michelle; Marchiori, Kristina; Aryobi, Suliman; Wener, Pam; White, Catherine; Larivière, Nadine; Isard, Roxanne; Chohan, Avneet; Forhan, Mary; Kiepek, Niki; Barbic, Skye; et al.
Background. Recent changes in the Canadian regulatory landscape have prompted reflections on the role and scope of occupational therapy in the provision of psychotherapy.Purpose. To document how psychotherapy has been explored in occupational therapy literature.Method. We conducted a scoping review following Preferred Reporting Items for Systematic Reviews and Meta-Analyses Scoping Review (PRISMA-ScR) guidelines by searching eight databases (e.g., Medline, AMED, CINAHL, EMBASE, PsycINFO, Cochrane Database of Systematic Reviews, Sociological Abstracts, and ProQuest Dissertations & Theses). Articles included at the full-text stage were subjected to a narrative synthesis.Findings. A total of 207 articles met the criteria for inclusion, spanning 93 years. 47.3% of these articles represented non-empirical literature, with only 14% representing effectiveness studies, suggesting that this body of literature remains in an early stage of development.Implications. Occupational therapists have been writing about and practicing psychotherapy for nearly a century, yet there remains an important opportunity to develop and evaluate occupation-based psychotherapy approaches. Effectiveness studies are needed.